2020
DOI: 10.1021/acsami.0c07394
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Artificial Synapse Consisting of Low-Surface Defect van der Waals and Self-Assembled Materials

Abstract: The long-term plasticity of biological synapses was successfully emulated in an artificial synapse fabricated by combining low-surface defect van der Waals (vdW) and self-assembled (SA) materials. The synaptic operation could be achieved by facilitating hole trapping and releasing only via the amine (NH2) functional groups in 3-aminopropyltriethoxysilane, which consequently induced a gradual conductance change in the WSe2 channel. The vdW–SA synaptic device exhibited extremely stable long-term potentiation/dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The human brain is mainly composed of a neural network consisting of around 10 11 neurons and around 10 15 synapses, making it robust, plastic, and fault-tolerant, and it has extremely low energy consumption (<20 W). Enlightened by the working mechanism of the brain, there have been many attempts to fabricate artificial neuromorphic electronics to imitate the behaviors of biological neural systems. As early as 1989, Mead proposed the concept of neuromorphic engineering, which is a nonbiological computing system with functions similar to the brain . With continuous development and expansion, neuromorphic engineering has become an interdisciplinary subject that draws inspiration from biology, physics, mathematics, computer science, and electronic engineering to design artificial nervous systems, based on the visual system, tactile systems, and multisensory integration, the physical architecture and design principles of which are based on the principles of the biological nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…The human brain is mainly composed of a neural network consisting of around 10 11 neurons and around 10 15 synapses, making it robust, plastic, and fault-tolerant, and it has extremely low energy consumption (<20 W). Enlightened by the working mechanism of the brain, there have been many attempts to fabricate artificial neuromorphic electronics to imitate the behaviors of biological neural systems. As early as 1989, Mead proposed the concept of neuromorphic engineering, which is a nonbiological computing system with functions similar to the brain . With continuous development and expansion, neuromorphic engineering has become an interdisciplinary subject that draws inspiration from biology, physics, mathematics, computer science, and electronic engineering to design artificial nervous systems, based on the visual system, tactile systems, and multisensory integration, the physical architecture and design principles of which are based on the principles of the biological nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Because 100 positive V WC pulses of +5 V were applied to the weight control terminal (T WC ), G post increased linearly from 0.6 to 27.8 nS. It also decreased gradually to the initial conductance level after applying 100 negative V WC pulses of −5 V. This result is quite impressive because an artificial synapse should have a multistate that can be modulated linearly and reproducibly for the successful implementation of a hardware neural network (HW-NN) (36)(37)(38)(39)(40)(41). This conductance response originates from the gradual ion movement inside the ion gel according to V WC (Fig.…”
Section: Flexible Synaptic Device Based On the Sizo/ion Gel Hybrid Structurementioning
confidence: 93%
“…In this light, the conductance difference representation between two equivalent devices can be one of the solutions to achieve both excitatory and inhibitory synaptic weights. [17,45,47] Next, the output values (f m ) were calculated using the sigmoid activation function (f (I m ) = 1 1+e −I m ) and compared with the corresponding label values (k m ). Finally, if necessary, the weight values were updated using the backpropagation algorithm (details are presented in the Experimental Section).…”
Section: Training and Inference Tasks For Acoustic And Emotional Patt...mentioning
confidence: 99%
“…[12][13][14] In recent years, for the implementation of HW-ANNs, numerous studies on artificial synapses with various structures have been reported. [15][16][17][18] Early research on artificial synapses has focused mostly on two-terminal nonvolatile memory devices based on a crossbar array structure, such as resistive random access memory, conductive bridge random access memory, and phase-change memory. [4,[19][20][21][22][23] This is because the crossbar array can be simply fabricated, easily expanded, and highly integrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation